INTRINSIC VS. EXTRINSIC MOTIVATION: WHICH DRIVES HIGHER PERFORMANCE IN HIGH-PRESSURE JOBS? - Rian Irvandi; Oktavianti; Rizki Eka Putra (RADJA PUBLIKA, 2025)
This study investigates the impact of intrinsic versus extrinsic motivation on performance and well-being in high-pressure professions. Against a backdrop of high burnout rates in fields like medicine and finance, the literature reveals a complex interplay: intrinsic motivation is linked to resilience and creativity, while extrinsic rewards can undermine intrinsic drive via the overjustification effect. Using a mixed-methods approach, this research combined quantitative surveys with qualitative interviews. Results demonstrated a strong positive correlation between intrinsic motivation and both high performance ratings and low burnout. Extrinsic motivation showed a more complex, curvilinear relationship. The discussion proposes a